PENINGKATAN LITERASI DIGITAL SISWA MA AL-WASHLIYAH DI ERA TRANSFORMASI TEKNOLOGI - Sinuraya, Khairul Abdi; Julita, Rina; Priyulida, Fitria; Andri Agus, Raja Tama (Smart Education, 2025)
Abstract: The rapid development of technology requires students to possess strong digital literacy skills to support their learning process. This community service activity at MA Al-Washliyah aims to enhance students’ abilities in utilizing technology effectively, critically, and safely. The training involved 28 students and was carried out in three stages. The first stage included a pre-test and an assessment of students’ initial digital skills. The second stage consisted of delivering materials through discussions, lectures, and hands-on practice related to searching for reliable information, using digital tools efficiently, and understanding digital ethics and safety. The final stage was evaluation through a post-test. The results showed a noticeable improvement in students’ ability to understand and use digital information, think more critically, and demonstrate greater awareness of digital safety and online footprints. This program is expected to help students better adapt to the demands of the technological transformation era and support their learning at future educational levels. Keywords: digital literacy; technological transformation; student; Abstrak: Perkembangan teknologi yang begitu cepat menuntut siswa untuk memiliki literasi digital yang baik dalam mendukung proses belajar. Kegiatan pengabdian kepada masyarakat di MA Al-Washliyah ini bertujuan meningkatkan kemampuan siswa dalam memanfaatkan teknologi secara tepat, kritis, dan aman. Pelatihan diikuti oleh 28 siswa dan dilaksanakan melalui tiga tahap. Tahap pertama adalah pretest serta identifikasi kemampuan awal siswa. Tahap kedua berisi penyampaian materi melalui diskusi, ceramah, dan praktik langsung terkait cara mencari informasi yang benar, menggunakan perangkat digital secara efektif, serta memahami etika dan keamanan dalam dunia digital. Tahap terakhir adalah evaluasi melalui posttest. Hasil kegiatan menunjukkan adanya peningkatan kemampuan siswa dalam memahami dan menggunakan informasi digital, berpikir lebih kritis, serta lebih sadar terhadap keamanan dan jejak digital. Kegiatan ini diharapkan dapat membantu siswa lebih siap menghadapi tantangan di era transformasi teknologi. Keywords: literasi digital, transformasi teknologi; siswa;